Determinant Factors of the Match-Based Internal Load in Elite Soccer Players. Issue 1 (2nd January 2021) - Enes, Alysson; Oneda, Gustavo; Alves, Danilo L.; Palumbo, Diogo de P.; Cruz, Ramon; Moiano Junior, José V. M.; Novack, Luiz F.; Osiecki, Raul
ABSTRACT: Purpose : To analyze the contribution of physical measures and external load in the match-based internal load of elite soccer players. Methods : Twenty-three elite soccer players (n = 23, age 26.69 ± 3.93 years, body mass 78.04 ± 5.03 kg, height 178.04 ± 5.19 cm, body fat 10.98 ± 1.25%) from a first division soccer team of the Brazilian Championship were evaluated first with anthropometric and physical measures (flexibility and muscle power of lower limbs), and after 24 hrs they were asked to perform an incremental treadmill test (VO2 max and ventilatory thresholds). Subsequently, athletes were monitored for 6 weeks during nine official matches of a regional championship. On match days, the external load data (e.g., player load) were collected by triaxial accelerometers with GPS systems and post 30 min after the end of the match the internal load was assessed with the Session Rating of Perceived Exertion method (Session-RPE). Results : Our main findings showed significant contributions of the Player Load (r = .62, p < .001; 42.3%) and Anaerobic Threshold (r = − .199, p = .05, 17%) for the predictive model of Session-RPE. Conclusions : Physical measures and external load have a significant influence on the internal load in elite soccer players. Our findings suggest that sport scientists can use the Session-RPE as a low-cost method for prescribing and monitoring training loads, by the influence of physical measures and external load on the match-based internal load, in order to optimize athletes' performance.